Distribution of disease courses in familial vs sporadic multiple sclerosis. (3rd December 2018) - Steenhof, Maria; Nielsen, Nete Munk; Stenager, Egon; Kyvik, Kirsten; Möller, Sören; Hertz, Jens Michael
Abstract : Objectives: The overall distribution of disease courses in multiple sclerosis (MS) is well established, but little is known about the distribution among familial MS cases. We examine the frequency of the different MS courses among familial and sporadic MS cases and determine whether MS cases within the same family had the same age at diagnosis and have experienced the same disease course. Materials and methods: This is a nationwide register study, based on data from the Danish MS Registry, the Danish Civil Registration System, and the Danish National Patient Registry. The main variables are MS diagnosis, MS course, and first‐degree relatives with MS The statistical analyses were carried out using logistic regression analysis, Kappa coefficient, and intraclass correlations coefficient. Results: In total, 7402 MS cases were included in the study, of which 531 have an affected first‐degree relatives, and 6871 are sporadic. We found that relapsing‐remitting MS including secondary progressive MS was more common among familial MS cases than among sporadic MS cases (Odds ratio = 1.64, 95% CI: 1.20‐2.24, P  = 0.002). We subsequently analyzed data on 133 MS families and found that MS courses correlate between the first and the second MS case diagnosed, while age at diagnosis does not. Conclusion: Familial MS cases are more likely to have relapsing‐remitting MS than a progressive course compared to sporadic MS cases. Secondly, we find that within MS families, first‐degree relatives are likely to have the same MS course, but we do not find that they are diagnosed at the same age.